ANALISIS UJI BENDING PADA PENGELASAN BAJA ST37 MENGGUNAKAN LAS SMAW (SHIELD METAL ARC WELDING) DENGAN POSISI PENGELASAN 1G - Rahmat Maulid; Tuparjono Tuparjono; yuli Dharta (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The welding process is the process of joining two or more metal materials in one unit in the presence of heat energy, the heat energy generated from the welding process can affect the results of the weld. In this study, the parameters used are variations in welding current and the number of layers and passes, the welding current used is 65A penetration, 95A fill-capping, 65A penetration, 115A fill-capping, 65A penetration, 125A fill-capping and the number of layers and passes required. used are 4 layer 7 pass and 4 layer 9 pass with DCEP (Direct Current Electrode Positive) polarity. In this study, a bending test analysis was carried out on ST37 steel welding using SMAW (Shield Metal Arc Welding) welding with a welding position of 1G. The purpose of this study was to determine the compressive strength of ST37 steel after the SMAW welding process with bending testing. The method used in the bending test uses the three point bending method. From the results of the bending test, the highest compressive load strength occurred at a welding current of 65A penetration, 125A fill-capping with 4 layers 7 passes, with a suppression load of 75.8kg.